Unusual Evolution of Thoracoabdominal Traumatism - Cottini, Guillermo (Cirugía del Uruguay, 1980)
A 53 - year - old patient entered hospital suffering from paroxysmal dyspnea, temperature and pain on the right side. A simpie X - ray indicated right hemithorax as totally blurred.